Market facilitation by local government and firm efficiency: Evidence from China - Cull, Robert; Xu, Lixin Colin; Yang, Xi; Zhou, Li-An; Zhu, Tian (Journal of Corporate Finance, 2017)
We use data from a large survey of Chinese firms to investigate whether local government efforts to facilitate market development improve firm efficiency. Both government provision of information about products, markets, and innovation and government assistance in arranging loans are positively associated with firm efficiency, and those private firms with weak access to and knowledge of financial, input, and product markets benefit most from such assistance. These patterns are robust across multiple estimation approaches. Our examination of the determinants of local government facilitation also suggests that it gravitates toward promoting efficiency, though there are also indications that rent-seeking may play a role. Our evidence is consistent with the notion that government facilitation can help some firms overcome market failures in the early stages of a country's private sector development. Though causality is difficult to establish, we argue that changing fiscal dynamics that forced local governments to become increasingly self-reliant in generating revenue, and a government promotion system based on local economic performance, were key motivating factors for market facilitation by local government officials.